Quantifying Tradeoffs Associated with Hydrologic Environmental Flow Methods1. (14th July 2015) - McKay, S. Kyle
Abstract: Freshwater management requires balancing and tradingoff multiple objectives, many of which may be competing. Ecological needs for freshwater are often described in terms of environmental flow recommendations (e.g., minimum flows), and there are many techniques for developing these recommendations, which range from hydrologic rules to multidisciplinary analyses supported by large teams of subject matter experts. Although hydrologic rules are well acknowledged as overly simplified, these techniques remain the state‐of‐the‐practice in many locations. This article seeks to add complexity to the application of these techniques by studying the emergent properties of hydrologic environmental flow methodologies. Two hydrologic rules are applied: minimum flow criteria and sustainability boundaries. Objectives and metrics associated with withdrawal rate and similarity to natural flow regimes are used to tradeoff economic and environmental needs, respectively, over a range of flow thresholds and value judgments. A case study of hypothetical water withdrawals on the Middle Oconee River near Athens, Georgia is applied to demonstrate these techniques. For this case study, sustainability boundaries emerge as preferable relative to both environmental and economic outcomes. Methods applied here provide a mechanism for examining the role of stakeholder values and tradeoffs in application of hydrologic rules for environmental flows.